Investigation on hardness and microstructural behavior of mahogany–brass reinforced bio-composite brake pads under varying compaction pressure - Fatkhurrohman Fatkhurrohman; Rizqa Ruviana; Musyaroh Musyaroh; Anisah Nurul Izzah (Politeknik Negeri Lhokseumawe, 2026)
The gradual elimination of asbestos in brake pad manufacturing has intensified the search for sustainable and non-toxic friction materials. This study presents waste-based bio-composite brake pads reinforced with mahogany sawdust and brass shavings, fabricated using a compaction-sintering approach. The scientific novelty of this study lies in the combined influence of reinforcement composition and compaction pressure on the microstructure-hardness relationship of wood-metal hybrid composites for brake pad applications. The effects of varying mahogany-to-brass ratio and compaction pressure on Shore D hardness and morphological characteristics were systematically evaluated. The results showed that increasing compaction pressure and reinforcement proportion improved composite densification and interfacial bonding, thereby increasing hardness. Increased hardness indicates better structural integrity and load-bearing capacity, which are important mechanical requirements for brake pad materials. The highest hardness value of 76.6 Shore D was obtained at a pressure of 3400 psi with a 4:4 composition, while the lowest value of 70.6 Shore D occurred at 3000 psi with a 1:4 ratio. These findings highlight the role of controlled compaction and balanced hybrid reinforcement in tailoring the mechanical characteristics of sustainable brake pad composites, supporting the potential utilization of wood and metal waste as environmentally friendly friction material components.